Moving to the Outskirts: Interplay Between Regulatory T Cells and Peripheral Tissues - Estrada Brull, Anna; Panetti, Camilla; Joller, Nicole (Frontiers in Immunology, 2022)
Regulatory T cells (Tregs) restrain excessive immune responses and dampen inflammation. In addition to this classical immune suppressive role, Tregs in non-lymphoid tissues also promote tissue homeostasis, regeneration and repair. In this review, we outline our current understanding of how Tregs migrate to peripheral tissues and the factors required for their maintenance at these sites. We discuss the tissue-specific adaptations of Tregs at barrier and immuno-privileged sites and the mechanisms that regulate their function within these organs. Furthermore, we outline what is known about the interactions of Tregs with non-immune cells in the different peripheral tissues at steady state and upon challenge or tissue damage. A thorough understanding of the tissue-specific adaptations and functions of Tregs will potentially pave the way for therapeutic approaches targeting their regenerative role.